(untitled) (Bangladesh Pharmaceutical Journal, 2020)
The present study was conducted to evaluate the antioxidant, antidiarrheal and analgesic activities of Vachellia farnesiana (L.) Wight & Arn. The methanol extract of V. farnesiana and its different fractionates were subjected to in-vitro assay for the determination of total phenolic content and antioxidative potential. The ethyl acetate soluble fraction (EASF) exhibited the highest free radical scavenging capacity (IC50 value of 21.49 ± 1.04 μg/ml) as compared to that exhibited by the standard butylated hydroxyl toluene (BHT) (IC50 value of 20.41 ± 0.05 μg/ml). Such prominent antioxidative potential was further reinforced by a phenolic content of 39.26 ± 0.85 mg of gallic acid equivalent per gram of extract. The plant extract, at the dose of 400 mg/kg body weight, reduced castor oil-induced diarrhea in mice model by a statistically significant (p < 0.05) margin of 47.62%, while the standard loperamide produced 66.67% reduction of diarrheal feces. The central and peripheral analgesic activities of the crude methanol extract of V. farnesiana (MEVF) was determined by tail flick- and acetic acidinduced writhing methods, respectively, in Swiss albino mice. In the tail flick method, oral administration of MEVF at doses of 200 and 400 mg/kg body weight exhibited 221.09 and 237.09% elongation of pain response time, respectively, after 90 minutes of administration whereas the standard morphine effectuated 518.34% elongation within the same time. Furthermore, the same doses of the extract illustrated 63.27 and 69.39% reductions, respectively, in the acetic acid-induced abdominal constrictions in mice. Compared to the standard acetylsalicylic acid with 75.51% inhibition, statistically significant (p < 0.05) peripheral analgesic activity was established. The results of the present investigations suggest that methanol extract of V. farnesiana possesses antioxidant, antidiarrheal and analgesic activities which eventually indicates the presence of biologically important phytoconstituents within the plant that needs further exploration. Bangladesh Pharmaceutical Journal 23(2): 181-186, 2020